HAMBATAN BONGKAR-MUAT KAPAL DALAM KEGIATAN EKSPOR-IMPOR DI PELABUHAN TANJUNG PRIOK JAKARTA - Nasywa Isbah Hidayah; Dinar Nur Aisah; Adzra Yumna Syabriani (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The development of globalization has caused a hindrance in the loading and unloading process of export and import goods, necessitating an improvement to reduce or overcome the challenges faced. The research in this journal employs a literature review involving analyses of journals and articles related to obstacles in the loading and unloading process of export-import activities at Tanjung Priok Port. This research is conducted by searching through various journal and article databases. It is an effort to identify obstacles in the loading and unloading process of goods in export-import activities at Tanjung Priok Port. Tanjung Priok Port remains a gateway to the national economy to date. However, besides that, the port also encounters various obstacles. Some obstacles occur primarily due to the low capabilities of human resources and the inefficient tools used in loading and unloading activities. This obstacle needs improvement, both in terms of human resources and facilities. Adequate facilities and qualified human resources can contribute positively to the smooth operation of activities at Tanjung Priok Port, especially in loading and unloading activities.